Petrological evidence for shock‐induced high‐P metamorphism in a gabbro. (25th November 2016) - Yang, J.‐J.; Zhang, H.‐R.; Chen, A.‐P.; Huang, M.‐X.
Abstract: Microlites (minute spherulitic, dendritic, skeletal, acicular and poikilitic crystals) diagnostic of crystallization in quenched melt or glass in fault rocks have been used to infer fossil earthquakes. High‐ P microlites and crystallites are described here in a variably eclogitized gabbro, the wallrock to the coesite‐bearing eclogite breccia at Yangkou in the Chinese Su‐Lu high‐ P metamorphic belt. The studied hand specimens are free of discernible shear deformation, although microfractures are not uncommon under the microscope. In the least eclogitized gabbro, the metagabbro, stellate growths of high‐ P minerals on the relict igneous minerals are common. Dendritic garnet crystals (<1−5  μ m) grew around rutile and/or phengite replacing ilmenite and biotite, respectively. Skeletal garnet also rims broken flakes of igneous biotite and mechanically twinned augite. Radial intergrowths of omphacite and quartz developed around relict igneous orthopyroxene and are rimmed by skeletal or poikilitic garnet where a Ti‐bearing mineral relict is present. Acicular epidote, kyanite and phengite crystallites are randomly distributed in a matrix of Na‐rich plagioclase, forming the pseudomorphs after igneous plagioclase. In the more eclogitized gabbro, the coronitic eclogite located closer to the eclogite breccia, all the igneous minerals broke down into high‐ P assemblages. Thick coronas of poikilitic garnet grew between the pseudomorphs after igneous plagioclase and ferromagnesian minerals. The igneous plagioclase is replaced by omphacite crystallites, with minor amounts of phengite and kyanite. Thermodynamic modelling of the plagioclase pseudomorphs shows an increase in P–T in the wallrock from the metagabbro to the coronitic eclogite, and the P–T variation is unrelated to H2 O content. The fluid‐poor pressure overstepping scenario is unsupported both by phase diagram modelling and by whole‐rock chemical data, which show that the various types of eclogitized gabbro are all fairly dry. A large pressure difference of >2 GPa between the metagabbro and the coesite‐bearing eclogites ~20 m apart cannot be explained by the subduction hypothesis because this would require a depth difference of >60 km. The microlites and crystallites are evidence for dynamic crystallization due to rapid cooling because constitutional supercooling was unlikely for the plagioclase pseudomorphs. The lack of annealing of the broken biotite and augite overgrown by strain free skeletal garnet is consistent with a transient high‐ P–T event at a low ambient temperature (<300 °C), probably in the crust. Therefore, the eclogitization of the wallrock to the eclogite breccia was also coseismic, as proposed earlier for the eclogite facies fault rocks. The outcrop‐scale P–T variation and the transient nature of the high‐ P–T event are inconsistent with the other existing tectonic models for high‐ P metamorphism. The fact that the less refractory but denser biotite is largely preserved while the more refractory but less dense plagioclase broke down completely into high‐ P microlite assemblages in the metagabbro indicates a significant rise in pressure rather than temperature. Given that the metamorphic temperatures are far below the melting temperatures of most of the gabbroic minerals under fluid‐absent conditions, stress‐induced amorphization appears to be the more likely mechanism of the coseismic high‐ P metamorphism.